The Effectiveness of Using WordPress CMS as an Interactive Learning Media on Students' Mathematical Problem Solving Ability - Chaerul Alfat; Saluky; Widodo Winarso (Universal Education, 2025)
Students’ mathematical problem-solving abilities remain low due to the lack of interactive media and technological limitations in learning. Previous studies have primarily focused on the practicality, validity, and effectiveness of learning media in improving student achievement. This study offers a new contribution by specifically examining the effectiveness of WordPress-based CMS in enhancing students’ mathematical problem-solving skills. The research aims to investigate the effectiveness of using WordPress CMS as an interactive learning medium for students at MTs Negeri 11 Cirebon. A quasi-experimental design was employed, involving an experimental group using WordPress CMS and a control group using conventional media. The findings indicate that students’ acceptance of the WordPress-based learning media was in the good category (86.32%). There was an increase in post-test scores (86.05) compared to pre-test scores (31.67), with classical mastery reaching 93%. The effect test showed that the use of WordPress CMS had a significant influence on problem-solving ability, contributing 64.6%. An independent sample t-test revealed a significant difference between the experimental and control classes, with an N-Gain of 79.28% (effective) in the experimental group and only 22.6% (ineffective) in the control group. The study is limited by its sample scope and the specific features of CMS used. The findings suggest that WordPress CMS can serve as an innovative tool in digital mathematics learning, providing a more interactive and effective learning experience. Academically, this study enriches the discourse on digital media development and encourages the integration of CMS platforms into technology-based mathematics instruction.